A Comparative Analysis of Growth Dynamics Among BRICS: Structural Challenges and Economic Opportunities - KERRAR, Mohamed Abdelghani; LAHOUEL, Ali (Journal of Excellence for Economics and Management Research, 2025)
The BRICS bloc, comprising Brazil, Russia, India, China, and South Africa, represents a significant economic force in the global economy. Through a comparative analytical approach, this study examines growth dynamics, structural challenges, and economic opportunities within BRICS nations, focusing on their divergent economic trajectories and collective ability to address global economic challenges. The study highlights the role of technological innovation, infrastructure investment, human capital development, and trade agreements in shaping the economic performance of BRICS countries. While China and India have demonstrated strong growth through state-led policies and economic liberalization, Brazil, Russia, and South Africa face persistent challenges such as political instability and resource dependency. The study concludes that addressing structural disparities, enhancing intra-BRICS trade, and strengthening institutional coordination are crucial for maintaining the bloc’s cohesion and increasing its global influence. Without these reforms, BRICS risks remaining a symbolic alliance with limited economic impact